Instabilidade de estruturas metálicas planas compostas de perfis de chapa dobrada - Almeida, Sandro Borges de (1989)
A numerical procedure to the analysis of plane trussed and/or framed structures constitued by cold-formed steel members of stiffned "U" shaped cross section is presented in this work. The structural behaviour is analyzed by means of a geometric nonlinear finit element model which takes also into account an additional nonlinearity due to local "U" section buckling effect. The solution of the nonlinear problem is obtained through a hibrid numerical scheme: incremental/iterative (tangent method) combined which a direct approach (secant method). The resulting mathematical-numerical model is assessed by experimental results from bending-compression tests perfomed on cold-formed steel columns. The proposed procedure is applied to several practical examples of plane trusses to demonstrate its potentiality.